Yield of herbicide tolerant sunflower hybrids due to the different herbicide treatments - Vígh, Tímea; Kerekes, Gábor; Hoffmann, Richard; Kazinczi, Gabriella (Acta Agraria Debreceniensis, 2010)
Sunflower is our most important oil-plant grown on the largest area in Hungary. In Europe sunflower has been grown since the 16th century. In recent years sunflower growing area is between 450-500 thousand hectares. Weed management in sunflower production is getting more and more difficult in case of annual and perennial dicotyledonous weeds, especially in dry springs. Two active ingredients, imazamox and tribenuron-methyl could be a solution for farmers for the control of these weeds in herbicide tolerant sunflower hybrids (Christensen-Reisinger 2000, Hódi-Torma 2004, Nagy et al. 2006). Most of the farmers choose the Clearfield technology and the use of tribenuron-methyl herbicides. In 2009 imazamox- (IMI) and tribenuron-methyl- (SU) tolerant sunflower hybrids were produced on 200 hectares in Hungary, of which 150 hectares was IMI, while 50 hectares was SU-hybrids. Small plot experiments were carried out to investigate the phytotoxicity of herbicides on imazamox (IMI) and tribenuron-methyl (SU) tolerant sunflower hybrids under field conditions. At harvest we measured the moisture content of achenes and average yield.